2022
DOI: 10.3390/foods11213372
|View full text |Cite
|
Sign up to set email alerts
|

Soybean-Derived Tripeptide Leu–Ser–Trp (LSW) Protects Human Vascular Endothelial Cells from TNFα-Induced Oxidative Stress and Inflammation via Modulating TNFα Receptors and SIRT1

Abstract: Soybean is a rich source of high-quality proteins and an excellent food source of bioactive peptides. A tripeptide, Leu–Ser–Trp (LSW), was previously identified from soybean as an angiotensin-converting enzyme inhibitory peptide. In the present work, we further studied its antioxidant and anti-inflammatory activities in human vascular endothelial cells (EA.hy926) and elucidated the mechanisms underlying these biological activities. In tumor necrosis factor alpha (TNFα)-stimulated EA.hy926 cells, LSW significan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 57 publications
0
3
0
Order By: Relevance
“…Given that the antihypertensive effects of IRW may result from elevated kynurenine levels, 11 we investigated the ACE2 upregulatory activity of kynurenine in cells. The doses of IRW and tryptophan were selected based on our previous studies, 24 while that of kynurenine was selected from a specific study where a concentration of 0.4 mM significantly increased ACE2 expression in two distinct lung epithelial cell types. 25 As shown in Figure 7B, both IRW and kynurenine significantly upregulated the ACE2 protein level in EA.hy926 cells.…”
Section: ■ Resultsmentioning
confidence: 99%
“…Given that the antihypertensive effects of IRW may result from elevated kynurenine levels, 11 we investigated the ACE2 upregulatory activity of kynurenine in cells. The doses of IRW and tryptophan were selected based on our previous studies, 24 while that of kynurenine was selected from a specific study where a concentration of 0.4 mM significantly increased ACE2 expression in two distinct lung epithelial cell types. 25 As shown in Figure 7B, both IRW and kynurenine significantly upregulated the ACE2 protein level in EA.hy926 cells.…”
Section: ■ Resultsmentioning
confidence: 99%
“…In addition, active peptides from soybeans have been reported to be effective at treating various diseases [6]. The soybeanderived tripeptide, Leu-Ser-Trp (LSW), ameliorates vascular endothelial oxidative stress and inflammatory responses [11]. In a recent study, it was observed that traditional Korean fermented soybean foods, such as doenjang, demonstrated protective effects against colitis induced by dextran sulfate sodium (DSS) in a mouse model [12].…”
Section: Introductionmentioning
confidence: 99%
“…In addition, active peptides from soybeans have been reported to be effective in treating various diseases [6]. The soybean-derived tripeptide, Leu-Ser-Trp (LSW), ameliorates vascular endothelial oxidative stress and inflammatory responses [11]. In a recent study, it was observed that traditional Korean fermented soybean foods, such as doenjang, demonstrated protective effects against colitis induced by dextran sulfate sodium (DSS) in a mouse model [12].…”
Section: Introductionmentioning
confidence: 99%